2017
DOI: 10.1007/s40292-017-0235-y
|View full text |Cite
|
Sign up to set email alerts
|

Perception, Knowledge, and Attitude toward Physical Activity Behaviour: Implications for Participation among Individuals with Essential Hypertension

Abstract: Majority of participants reported good perceptions of PA behavior, in terms of not being discouraged by relations and friends, and of its benefits. They reported good knowledge about PA behavior. The participants demonstrated positive attitude in terms of benefits, importance, and involved risk of PA, and reported high level of participation in PA. There were significant correlations among knowledge about PA, attitude towards PA and participation in PA. PA level generally correlated significantly with attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 28 publications
5
23
0
1
Order By: Relevance
“…KAB evaluation, which is considered the first step of behavioral education, can help health educators grasp individuals' understanding, health beliefs, and actions taken regarding a specific health issue, and provide the scientific basis for the development of intervention plans. The knowledge of health-related behaviors was reported to influence individuals' attitudes and practices in health management [5]. Specifically, assessing diet-related knowledge, attitudes, and behaviors was of vital importance in dietary health promotion at the population level [6][7][8], and thus it should be a necessary prerequisite for the implementation of dietary intervention in China.…”
Section: Introductionmentioning
confidence: 99%
“…KAB evaluation, which is considered the first step of behavioral education, can help health educators grasp individuals' understanding, health beliefs, and actions taken regarding a specific health issue, and provide the scientific basis for the development of intervention plans. The knowledge of health-related behaviors was reported to influence individuals' attitudes and practices in health management [5]. Specifically, assessing diet-related knowledge, attitudes, and behaviors was of vital importance in dietary health promotion at the population level [6][7][8], and thus it should be a necessary prerequisite for the implementation of dietary intervention in China.…”
Section: Introductionmentioning
confidence: 99%
“…According to the health belief model, knowledge regarding health behaviour is a strong modifying factor for healthy lifestyle, however it should be combined with other factors such as good perceptions, positive health attitudes and many other conditions such as socioeconomic factors [15]. Studies also have revealed knowledge of specific risk factors is associated with healthy behaviour, however, knowledge alone does not motivate behavioural change [16][17][18][19]. The Heart disease fact questionnaire which was designed and validated by Wagner et al (2005) and has been commonly used for the assessment of knowledge of CV risk factors knowledge [20].…”
Section: Introductionmentioning
confidence: 99%
“…KAB evaluation is considered the first step of health behavior education, which can grasp the individual's understanding, health beliefs, and actions taken regards a specific health issue, and then provide scientific basis for the development of intervention plan. Adequate knowledge of health-related behavior has been reported to influence the patient's attitude and practice in health management [5]. Specifically, assessing diet-related knowledge, attitude, and behaviors has been reported to be vitally important in achieving dietary health promotion at the population level [6][7][8], thus should be a necessary prerequisite for dietary intervention in China.…”
Section: Introductionmentioning
confidence: 99%